2016
DOI: 10.1098/rstb.2015.0319
|View full text |Cite
|
Sign up to set email alerts
|

The underestimated biodiversity of tropical grassy biomes

Abstract: One contribution of 15 to a theme issue 'Tropical grassy biomes: linking ecology, human use and conservation'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 68 publications
0
108
0
6
Order By: Relevance
“…We could not find differences based on the level of threat, and only estimates from Madagascan or savanna species were significantly less correlated between data sources. The fact that only very few rodent species are present in Madagascar, and that savannas’ biodiversity tended to be historically neglected (Murphy, Andersen, & Parr, ), may explain why more uncertainty exists in these regions. We observed that correlations were generally lower for elevation than for climatic variables, especially for lowland species.…”
Section: Discussionmentioning
confidence: 99%
“…We could not find differences based on the level of threat, and only estimates from Madagascan or savanna species were significantly less correlated between data sources. The fact that only very few rodent species are present in Madagascar, and that savannas’ biodiversity tended to be historically neglected (Murphy, Andersen, & Parr, ), may explain why more uncertainty exists in these regions. We observed that correlations were generally lower for elevation than for climatic variables, especially for lowland species.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring natural regeneration until some of the secondary savanna characteristics reach old‐growth savanna values and subsequently removing trees to avoid the thickening of the vegetation (Brudvig, ) may be the most adequate restoration strategy because it has relatively low costs and at least maintains the old‐growth savanna structure and part of its animal and plant diversity, which requires an open habitat to survive (Abreu et al., ; Durigan & Ratter, ; Murphy, Andersen, & Parr, ; Veldman et al., ). The reintroduction of fire to secondary Neotropical savannas may be equally effective to avoid vegetation thickening, but further studies are needed to optimize this management practice because exotic grasses change fire behaviour (Gorgone‐Barbosa et al., ) and may have undesirable effects on secondary savannas.…”
Section: Discussionmentioning
confidence: 99%
“…However, universally, the flora is shade intolerant, at least at the establishment phase, due to the open canopy overstorey [45]. While the biodiversity value of these systems to-date has been typically overshadowed by that of tropical forests [26], Murphy et al [42] illustrate the biodiversity value of TGBs, particularly of vertebrates and range-restricted species, and emphasize variation in diversity among the TGB regions (the South American region generally being the richest).…”
Section: Defining Tropical Grassy Biomesmentioning
confidence: 99%
“…For the first time, analyses are presented on the biogeography and potential distributions of Asian savannahs [39]. Other significant steps forward in our understanding include: methods for characterizing ancient versus derived grassy biomes [40,41], comparative data on the species diversity of TGB regions across the globe [42], an improved understanding of the complex ecology of herbivory and fire [16,43] and the context-dependent response of vegetation to global change [44], and finally, tools to examine trade-offs in biodiversity, carbon and agriculture to aid land-use planning and policy [10].…”
Section: This Issuementioning
confidence: 99%
See 1 more Smart Citation